Glass fiber reinforced gypsum composites with microencapsulated PCM as novel building thermal energy storage material. (18th July 2022) - Gencel, Osman; Hekimoglu, Gökhan; Sarı, Ahmet; Ustaoglu, Abid; Subasi, Serkan; Marasli, Muhammed; Erdogmus, Ertugrul; Memon, Shazim Ali
Highlights: Microencapsulated PCM (mPCM) was used at 2.5, 5 and 7.5 wt% in glass fiber reinforced gypsum plasterboard (GP). GP with 7.5 wt% mPCM has latent heat of 16.7 and 16.6 J/g at melting and solidification of 11.90 °C and 12.09 °C, respectively. mPCM-GP room showed 3 °C lower temperature compared to the reference room. mPCM-GP can be considered as an effective energy-saving material in buildings. Abstract: A comprehensive study involving the fabrication and characterization of gypsum plasterboards combined with microencapsulated phase change material (mPCM) is introduced to evaluate their benefits regarding thermoregulation management and energy saving performance in buildings. For this purpose, the produced new type of gypsum plasterboard was subjected to the detailed chemical, morphological, mechanical, physical and thermal tests. The gypsum plasterboard incorporated with mPCM (7.5 wt%) and reinforced by glass fiber has latent heat capacities as high as 16.7 and 16.6 J/g at onset melting and solidification temperature of 11.90 °C and 12.09 °C, respectively. TGA analyzes revealed high thermal stability of gypsum plasterboard up to about 140 °C. Outcomes exhibited that mPCM-gypsum plasterboard can substantially diminish cooling load of a building during the daytime even at the high room temperature and offer decline in heat necessity of a house during night-time. During peak room temperature hours, the mPCM-gypsum plasterboard achieved 3 °C lower temperatures than the reference room, and it provided a cooler room temperature for about 7 h during the daytime while a warmer temperature of 0.3 °C was achieved at the cold weather. As a result, the produced gypsum-based composites can be considered as an energy-saving and indoor temperature regulating material in buildings.